Dose-dependent nephroprotective effects of turmeric extract against diclofenac-induced kidney injury in rats - Renya Rosari Amapiran; Anita Lidesna Shinta Amat; Desi Indriarini; Syeben HE Hietingwati; Tri Nugraheni (Indonesian Society for Biochemistry and Molecular Biology, 2025)
Background: Non-steroidal anti-inflammatory drugs, particularly diclofenac sodium, are widely prescribed but can cause nephrotoxicity through oxidative stress mechanisms. Turmeric (Curcuma longa L.) contains curcumin and other bioactive compounds with potent antioxidant properties that may protect against drug-induced kidney damage. Objective: To evaluate the dose-dependent effects of turmeric ethanol extract on kidney histopathology in rats with established diclofenac sodium-induced nephrotoxicity. Methods: Twenty-eight male Sprague Dawley rats were randomly divided into four groups: normal control, diclofenac (10 mg/kg for 7 days), and two treatment groups receiving diclofenac followed by turmeric extract at 100 mg/kg or 200 mg/kg for 14 days. Kidney histopathology was assessed using the Arsad scoring system by a blinded pathologist. Results: Significant differences existed between groups (p < 0.001). The negative control exhibited severe kidney damage with hydropic degeneration, granular casts, and cellular casts (mean score: 2.78 ± 0.24). Treatment with 100 mg/kg showed partial improvement (1.65 ± 0.31), while 200 mg/kg demonstrated substantial improvement approaching normal histology (0.52 ± 0.18) with only minimal residual damage. Conclusion: Turmeric extract demonstrates significant dose-dependent nephroprotective effects against diclofenac-induced kidney damage, with 200 mg/kg providing superior protection, suggesting potential therapeutic applications in mitigating NSAID-induced nephrotoxicity.